2021
DOI: 10.3390/cancers13010120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RECIST 1.1 and iRECIST in Patients Treated with Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Despite wide recognition of iRECIST, evidence regarding the impact of iRECIST over RECIST 1.1 is lacking. We aimed to evaluate the impact of iRECIST on assessing treatment efficacy of immune checkpoint inhibitors (ICIs) over RECIST 1.1. Articles that evaluated the treatment response and outcome based on both RECIST 1.1 and iRECIST were eligible. Data regarding overall response rates (ORR) and disease control rate (DCR) based on RECIST 1.1 and iRECIST, and data required to estimate individual patient data of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 38 publications
0
38
0
13
Order By: Relevance
“…The major difference between the various immune response criteria is the definition of pseudoprogression: while irRC and irRECIST only define PD after showing progression in two consecutive studies at least 4 weeks apart, iRECIST introduces a new concept of unconfirmed PD (iUPD) for new lesions, which can become later confirmed PD (iCPD) if there is a continued progression in the next imaging study in 4-8 weeks [18,22]. Some studies reported that iRECIST can capture atypical immune response and might show a modest benefit in the survival endpoint compared to RECIST that might underestimate the benefit of immunotherapy in some patients [19,[32][33][34][35], for instance, an underestimation rate of 12.8-15% was reported in advanced melanoma patients receiving pembrolizumab using RECIST 1.1 [36,37]. Further studies are necessary to compare between various immune response criteria and RECIST 1.1 and also to evaluate if the benefits of iRECIST can outweigh the increased burden in imaging interpretation, data management, and cost [33,34].…”
Section: Radiologic Evaluation Of Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The major difference between the various immune response criteria is the definition of pseudoprogression: while irRC and irRECIST only define PD after showing progression in two consecutive studies at least 4 weeks apart, iRECIST introduces a new concept of unconfirmed PD (iUPD) for new lesions, which can become later confirmed PD (iCPD) if there is a continued progression in the next imaging study in 4-8 weeks [18,22]. Some studies reported that iRECIST can capture atypical immune response and might show a modest benefit in the survival endpoint compared to RECIST that might underestimate the benefit of immunotherapy in some patients [19,[32][33][34][35], for instance, an underestimation rate of 12.8-15% was reported in advanced melanoma patients receiving pembrolizumab using RECIST 1.1 [36,37]. Further studies are necessary to compare between various immune response criteria and RECIST 1.1 and also to evaluate if the benefits of iRECIST can outweigh the increased burden in imaging interpretation, data management, and cost [33,34].…”
Section: Radiologic Evaluation Of Treatment Responsementioning
confidence: 99%
“…Some studies reported that iRECIST can capture atypical immune response and might show a modest benefit in the survival endpoint compared to RECIST that might underestimate the benefit of immunotherapy in some patients [19,[32][33][34][35], for instance, an underestimation rate of 12.8-15% was reported in advanced melanoma patients receiving pembrolizumab using RECIST 1.1 [36,37]. Further studies are necessary to compare between various immune response criteria and RECIST 1.1 and also to evaluate if the benefits of iRECIST can outweigh the increased burden in imaging interpretation, data management, and cost [33,34].…”
Section: Radiologic Evaluation Of Treatment Responsementioning
confidence: 99%
“…Another challenge in making an accurate response assessment is the emergence of atypical response patterns, such as pseudoprogression or hyperprogression, following immunotherapy. Therefore, radiologists should also be familiar with the incidence, criteria, and imaging features associated with these atypical response patterns [ 5 6 7 ]. Current immune response assessment criteria, such as the Immune Response Evaluation Criteria in Solid Tumors (iRECIST) or LYmphoma Response to Immunomodulatory therapy Criteria (LYRIC), may also have limitations in terms of providing accurate response assessment following immunotherapy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, radiologists should also be familiar with the incidence, criteria, and imaging features associated with these atypical response patterns [ 5 6 7 ]. Current immune response assessment criteria, such as the Immune Response Evaluation Criteria in Solid Tumors (iRECIST) or LYmphoma Response to Immunomodulatory therapy Criteria (LYRIC), may also have limitations in terms of providing accurate response assessment following immunotherapy [ 5 ]. Hence, significant efforts have been made to apply radiomics or artificial intelligence (AI) techniques to these evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…14 The iRE-CIST criteria were undoubtedly steps in the right direction, especially for patients who would be classified as progressive disease under previous RECIST criteria. 15 However, considering that only 20%-40% of patients respond to immunotherapy, there is a pressing need for reliable predictive biomarkers. 16 In comparison with other diagnostic modalities (e.g.…”
Section: Introductionmentioning
confidence: 99%